Motivation and religion - Karabenick, Stuart A.; Maehr, Martin L. (Advances in motivation and achievement, 2005)
Considerable evidence indicates that religion is a motivational force in the lives of most of the world's population, and recent social and political events have placed religion center stage. Motivation is considered an essential component of any adequate answer to the question, "Why religion?" That question concerned early psychologists, such as Freud and James, but was relatively neglected with the ascendancy of behaviorism. It has since regained momentum as an important area of research and scholarship. In spite of the fact that motivational principles are implicit in many analytical treatm.